The social representations of Algerian women by employing the formalistic propaganda approach on the folklore story - NADHER, Yamina (Social Sciences Journal)
The aim of this study is to highlight the image of the woman personality through the popular tales in the region of Tissemsilt (Algeria). These popular tales that lots of people believe no more than fictitious legends and myths. We note, moreover, that the popular tale reflects the life of peoples and expresses their ideas, it also has values and educational, sociological, psychological and historical acquirements.The study found that the popular tale mentioned several aspects of the woman personality, because it has shown, by employing the Propp morphological method, her important role in social life through her relationship with the family on one hand, and the whole community on the other.The results of the study came to confirm that the woman appeared as distinct and exceptional depiction in the popular tale, playing different roles with various characters expressing her psychological needs, in order to highlight her social position